Parallel text typology dataset - Östling, Robert; Kurfalı, Murathan (Stockholm University, 2023)
This repository contains data accompanying the paper Neural models can sometimes discover typological generalizations, currently being submitted for publication. It contains the following information for 1295 different languages:


language vector representations from a range of neural models

automatically derived lists of affixes

automatically derived lists of inflectional paradigms

typological features derived from annotation projection, and statistics on dependency relations

typological features derived from classifiers trained on language vectors and typological databases

automatically derived word lists

data needed for automatic evaluation of language representations (code in separate repository)

Note that the multilingual word embeddings described in the paper are very large, and therefore distributed in a separate public repository.

The computations were enabled by resources provided by the Swedish National Infrastructure for Computing (SNIC) at C3SE partially funded by the Swedish Research Council through grant agreement no. 2018-05973. This work was funded in part by the Swedish Research Council through grant agreement no. 2019-04129.
Keywords: computational typology; parallel text; multilingual NLP; Natural Language Processing; Språkbehandling och datorlingvistik